Safety and effectiveness of large volume coils in the treatment of small aneurysms. (20th January 2016) - Kulcsár, Zsolt; Wanke, Isabel; Rüfenacht, Daniel; Wetzel, Stephan G; Göricke, Sophia; Kolia, Kiriaki; Quarfordt, Steven; Calvert, Justin; Hawk, Harris; Baxter, Blaise
Abstract : Background and purpose: Large volume soft design coils facilitate quicker aneurysm filling and high packing density. Our purpose was to analyze the feasibility, safety, and effectiveness of the Penumbra Coil 400 (PC400) system in the treatment of small aneurysms. Materials and methods: A retrospective analysis of prospective data collected at three different centers was performed on consecutive aneurysms <10 mm treated with the PC400 system. A total of 92 aneurysms were included in the study. Feasibility, procedure safety, angiographic and clinical results, and follow-up results were evaluated. Results: Mean aneurysm size was 5.8±2.0 mm. An average of 2.5±1.3 coils with a mean length of 18±16 cm per aneurysm was used, resulting in a mean packing density of 45.6±14.4%. The thromboembolic event rate was 3.3% and no procedural aneurysm rupture was observed. Immediate adequate occlusion was achieved in 66% of aneurysms. During a mean follow-up period of 7.4 months the number of adequate occlusions increased to 91%. Conclusions: Large volume PC 400 coils are safe and effective in the treatment of small aneurysms with a low thromboembolic complication rate and no hemorrhagic events. High packing densities are achieved with a low average number of coils used per aneurysm treated. The aneurysms demonstrated progressive occlusion over time, which probably suggests stability in the long term.